ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN LIKUIDITAS DAN PROFITABILITAS PADA PT. KIMIA FARMA (PERSERO) Tbk - Aldino Syahputra; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Good working capital management determines the effectiveness and efficiency of the activities carried out by the company. This study aims to determine and analyze the effectiveness of working capital management in increasing liquidity and profitability at PT. Kimia Farma (Persero) Tbk. The type of data used in this study is quantitative data. The data source uses primary data obtained through interviews and secondary data using PT. Kimia Farma (Persero) Tbk for the period 2014-2018 and using ratio analysis.The results of the study are as follows: First, the management of working capital to liquidity which always decreases every year causes a decrease in the liquidity ratio as measured by the current ratio and fast ratio. This indicates a reduction in the company's financial ability to meet its short-term obligations. Second, the management of working capital to profitability causes a decrease in ROA which indicates the company's efforts to obtain reduced profits and ROE also decreases but sometimes increases which indicates the amount of profit in terms of investors.Keywords: Working Capital, Liquidity, Profitability